Acoustic and thermal analysis of geometrically different treated kenaf/polylactic acid green composite laminates. (December 2022) - Manral, Ankit; Bajpai, Pramendra K
Kenaf fiber reinforced polylactic acid green composites possess mentionable thermal and acoustic insulating properties. Sound transmission and sound absorption coefficients are the minimum required necessary parameters for predicting the acoustic properties while thermal conductivity is alone sufficient for predicting the thermal behavior of natural fiber reinforced green composites. In the present chapter, the effect of utilizing different types of kenaf fiber mats and their chemical treatment (sodium acetate) on the thermal and acoustic properties of developed composites is presented. The results showed that the thermal conductivity of developed composites increased with chemical treatment concentration and treatment time. Additionally, the geometry of kenaf fiber mats also influenced the thermal and acoustic properties of developed composites.